The Role of the Pelalawan Regency General Election Commission in Fulfilling the Political Rights of Persons with Disabilities Based on Law Number 7 of 2017 - Hafiz Sutrisno; Aminoel Akbar Novi Maimory (International Journal of Science and Environment (IJSE), 2024)
This study aims to analyze the role of the Pelalawan Regency General Election Commission (KPU) in fulfilling the political rights of persons with disabilities based on Law Number 7 of 2017 concerning General Elections. This study uses a sociological juridical approach, by examining the provisions of laws and regulations governing the political rights of persons with disabilities and their implementation at the regional level. The results of the study indicate that the Pelalawan Regency KPU has implemented various efforts to ensure the political participation of persons with disabilities, such as providing accessibility facilities at Polling Stations (TPS), involving groups with disabilities in election stages, and inclusive socialization. However, in its implementation, obstacles are still found, including the lack of supporting facilities, limited assistance staff, and low understanding of officers regarding the special needs of persons with disabilities. Therefore, policy strengthening and ongoing training are needed for election organizers to realize the implementation of disability-friendly and fair general elections in accordance with the principle of equal rights of citizens.